Corporate governance versus economic governance: banks and industrial restructuring in the US and Germany - Sigurt Vitols (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1995)
This paper critically examines the debate on corporate governance and the claim (often made in Anglo-American companies) that the close links between German banks and industry are primarily responsible for the longer-term investment strategies and greater quality competitiveness of German manufacturing. Instead, it is argued here that manufacturing investment and bank behavior must be examined within a broader system of economic governance. In particular the regulation of labor markets is a key factor influencing company choices between price and quality-competitive strategies. The corporatist regulation of German labor markets has encouraged quality-competitive strategies by keeping labor costs out of competition to a greater extent than in the US, where a collapse in pattern bargaining in core manufacturing industries and the strategic use of bankruptcy was motivated by companies' attempts to gain a comparative price advantage on the basis of lower labor costs. This argument is supported through a case study of the restructuring of the steel industry in Germany and the US in the 1980s. – – Gegenstand dieses Discussion Papers ist eine Untersuchung der These, daß die langfristig angelegten Investitionsstrategien und die hohe Wettbewerbsfähigkeit der deutschen Industrie primär den engen Beziehungen der deutschen Universalbanken zu Industrieunternehmen (Stichwort: Corporate Governance) zuzuschreiben sind. Im Gegensatz dazu wird hier die These vertreten, daß Investitionen und das Verhalten der Banken wesentlich von einem breiteren institutionellen Umfeld (Stichwort: Economic Governance System) abhängen. Vor allem ist die Regulierung des Arbeitsmarkts ein entscheidender Einfluß auf die Entscheidung in Unternehmen, ob die Produktionsstrategie auf niedrigen Kosten oder auf hoher Produktqualität basieren soll. Die korporatistische Regulierung des Arbeitsmarkts in Deutschland und die dadurch relativ geringe Möglichkeit, durch Lohnsenkungen Kostenvorteile gegenüber Konkurrenten zu erzielen, hat stark zu einer Qualitätsstrategie beigetragen. Im Gegensatz dazu haben in den USA große Industrieunternehmen Anfang der achtziger Jahre ihre auf freiwilliger Basis koordinierten Lohnverhandlungen aufgegeben und zum Teil Insolvenzverfahren eingeleitet, um Kostenvorteile zu erreichen. Dieses Argument wird durch eine vergleichende Fallstudie der Umstrukturierung in der usamerikanischen und deutschen Stahlindustrie in den achtziger Jahren unterstützt.
Keywords: 330; Industrie; Wirtschaftliche Anpassung; Corporate Governance; Staatliche Einflussnahme; Institutionalismus; Deutschland; USA